OPERATION OF HEAVY TRUCKS IN ADVERSE WEATHER CONDITIONS IN THE MINING SYSTEM (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The literature on the operation of heavy trucks in adverse weather conditions in mining systems highlights the significant challenges posed by weather-related disruptions. Studies focus on various weather conditions such as snow, ice, fog, and heavy rain, emphasizing the adverse effects on truck performance, safety, and operational efficiency. A common theme across the literature is the impact of reduced visibility and traction in harsh weather, which increases the risk of accidents and delays in mining operations. The research suggests that integrating advanced technologies such as traction control systems, autonomous vehicles, and real-time weather monitoring can mitigate these risks and improve operational resilience. Case studies from mining operations in regions like Australia and Canada provide practical examples of how these technologies and strategies have been successfully implemented, demonstrating tangible benefits in both safety and cost-effectiveness. Overall, the literature indicates a growing trend towards incorporating technological innovations and proactive strategies to manage the risks associated with adverse weather, emphasizing the need for a multi-faceted approach to ensure the safe and efficient operation of heavy trucks in mining environments.